Different methods of managing bluestem pastures. - Smith, E.F.; Anderson, K.L.; Baker, F.H.; Walker, G.L. (Kansas Agricultural Experiment Station, 2011)
This experiment was to determine effects of different stocking rates, deferred grazing, and pasture burning on livestock gains, productivity of pastures, and range condition as determined by plant population changes. In addition to the yearly report, a summary of the cattle gains for the first six years of this test is included.
Keywords: Beef; Bluestem pastures; Gains; Stocking rates